Freedom gas to Europe: Scenarios analyzed using the Global Gas Model - Ruud Egging-Bratseth; Franziska Holz; Victoria Czempinski (Research in International Business and Finance, 2021)
State-of-the-art, open access numerical modeling of imperfectly competitive energy markets offers a sound and transparent way to address topical research questions in energy and commodity markets. We use an open access equilibrium model, the Global Gas Model (GGM), and sector-specific, politically motivated scenarios to investigate the prospects for sales of liquefied natural gas (LNG) from the U.S. into the European energy market. We discuss the risks and opportunities for U.S. LNG and derive implications for policy, business, and finance in the energy sector. We find that Europe is not an attractive market for US LNG in the base case and in scenarios of moderate support of U.S. LNG flows into Europe. In these scenarios, Asia offers higher prices for US LNG and draws substantially higher import volumes. Our modeling results show that the interconnectedness of global gas markets due to an abundance of LNG import capacity in Europe and other regions—particularly Asia—allows for adjustments to global trade patterns that mitigate the consequences of regional disturbances.
Keywords: C61; L13; L95; Q34; Q37; Q48; 330; Numerical modeling; Natural gas; Liquefied natural gas; Energy policy; USA; Europe